The carpal pad as an alternative sampling site for blood glucose testing in dogs - Borin-Crivellenti, S. [UNESP]; Crivellenti, L. Z. [UNESP]; Tinucci-Costa, M. [UNESP] (Wiley-Blackwell, 2012)
To investigate the feasibility and validity of sampling blood from the carpal pad in hospitalised healthy and diabetic dogs. METHODS The carpal pad was compared to the ear as a sampling site in 60 dogs (30 healthy and 30 diabetic dogs). RESULTS Lancing the pads was very well tolerated. The average glucose concentrations in blood samples obtained from the ears and carpal pads exhibited a strong positive correlation (r = 0.938) and there were no significant differences between them (P = 0.914). In addition, 98.3% of the values obtained were clinically acceptable when assessed by the error grid analysis. CLINICAL SIGNIFICANCE The carpal pad is a good alternative sampling site for home monitoring, especially in animals with a soft and/or light-coloured pad.